2013
DOI: 10.3892/ol.2013.1376
|View full text |Cite
|
Sign up to set email alerts
|

Immune response, clinical outcome and safety of dendritic cell vaccine in combination with cytokine-induced killer cell therapy in cancer patients

Abstract: The aim of the present study was to determine the clinical value of autologous immunocyte therapy as a standard treatment regimen for patients with cancer. A total of 121 patients with cancer were included in this study. Subsequent to performing leukapheresis using the Fresenius Kabi System, 1×107 dendritic cells (DCs) for the vaccine and 1×109 cytokine-induced killer (CIK) cells for injection were prepared. An analysis of the immune phenotypes of HLA2DR, CD80 and CD83 for the DCs and of CD3, CD8 and CD56 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…A previous study proved that Pro-GRP is highly expressed in SCLC (10), and the specificity and sensitivity of Pro-GRP detection for SCLC diagnosis are higher than those of NSE (22,23). In line with this, the present study also indicated that Pro-GRP is a specific tumor marker of SCLC that had a relatively high expression prior to therapy and exhibited on obvious decrease thereafter.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A previous study proved that Pro-GRP is highly expressed in SCLC (10), and the specificity and sensitivity of Pro-GRP detection for SCLC diagnosis are higher than those of NSE (22,23). In line with this, the present study also indicated that Pro-GRP is a specific tumor marker of SCLC that had a relatively high expression prior to therapy and exhibited on obvious decrease thereafter.…”
Section: Discussionsupporting
confidence: 76%
“…Peripheral hematopoietic stem cells were expanded and DCs and CIKs were collected. The cell quantity was required to reach >1x10 10 and the cell activity >95%. The cells were suspended in 100 ml normal saline containing 20 g/l human serum albumin and injected back into the patient's body once per week for a total of three times.…”
Section: Dc-cik Biological Therapymentioning
confidence: 99%
“…A total of 1x10 7 DCs in 0.1 ml NS was administrated intradermally into the forearm of each patient. The patients were asked to measure the diameter of the skin erythema around the injection point following 24, 48 and 72 h. The DTH reaction was defined as follows: >10 mm in diameter, strongly positive; 5-10 mm, positive; 2-5 mm, weakly positive; and <2 mm, negative (22,28).…”
Section: Patientsmentioning
confidence: 99%
“…The supernatants were collected and used as a tumor lysate for DC preparation. DCs and CIK cells were prepared as described in a previous study (22)(23)(24). The supernatants of cultured PBMCs were removed for the additional preparation of CIK cells and the remaining cells were cultured for 7 days in the presence of granulocyte-macrophage colony stimulating factor, interleukin (IL)-4 and tumor necrosis factor (PeproTech EC, Ltd., London, UK), and pulsed with the tumor lysate (PeproTech EC, Ltd.) (25).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were cultured overnight, then adherent cells (including monocytes) and suspension cells (including lymphocytes) were collected separately (14)(15)(16).…”
Section: Preparation Of Cellsmentioning
confidence: 99%